UZLUKSIZ KASBIY RIVOJLANISH TO‘G‘RISIDA AYRIM MULOHAZALAR - Davronov Pirnazar Ziyatovich; Umarov Sanjar Sunnatovich (FAN, TA'LIM VA AMALIYOT INTEGRATSIYASI, 2022)
The article presents the introduction of continuous professional development of teachers, forms of advanced training, an individual trajectory of the professional development of an employee, an electronic portfolio, components of the trajectory, an algorithm for its construction and graphs that display continuous professional development.